Rogue waves in magnetic metamaterials with intersite coupling nonlinear effects - Amadou, Yaouba; Douvagai; İnç, Mustafa; Abas, Siti Sabariah Binti; Joseph, Mora; Alsawalha, Mohammad; Doka, Serge Y. (Elsevier, 2026)
In this study, we investigate rogue waves in nonlinear magnetic metamaterials influenced by the intersite coupling and nonlinearity. Using the perturbation method, we derive the cubic-quintic nonlinear schr & ouml;dinger equation. Similarity and Darboux transformations give rogue wave solutions. The acquired rogue wave solutions are plotted, and we analyze that the intersite coupling strength and nonlinearity affect the rogue waves by maintaining constant their amplitude thresholds, and modifying their localization profiles. The results provide insight into tailoring extreme wave events in engineered metamaterials and offer a theoretical foundation for controlling nonlinear energy transport at the nanoscale.
Keywords: Magnetic metamaterial; Darboux transformation; Intersite coupling effect; Nonlinear effect; Rogue waves